Optimization of Islamic Religious ‎Education Through Corpse ‎Muhammad Training at ‎Muhammadiyah 25 Senior High ‎School - Fadhil Zainurraziq; Nur Aqsara Mahdani (el-Tarbawi : Jurnal Pendidikan Agama Islam, 2025)
Islamic Religious Education (PAI) plays a crucial role in shaping students' character and spirituality, as well as equipping them with practical skills useful in community life. Among these crucial skills, the embalming of the body a collective obligation (fardhu kifayah) in Islam—is rarely taught in- depth in schools. Beyond providing religious knowledge, this skill also strengthens students' sense of social responsibility within the Muslim community. This community service program aims to improve the understanding and skills of students at Muhammadiyah 25 Pamulang High School in carrying out embalming of the body through Participatory Action Research (PAR)-based training. The PAR approach allows students to actively engage in practical learning, where they not only learn theory but also practice each stage of embalming the body, from washing and shrouding to burial, in accordance with Islamic law. The training results show a significant increase in students' skills and understanding, as well as an increased awareness of their social responsibility as members of the Muslim community. In addition to improving the quality of Islamic Religious Education (PAI) learning, this program serves as a model for applicable and participatory education, which is expected to be continuously integrated into the school curriculum. By providing hands-on experience and understanding of religious obligations, this training equips students with valuable life skills and prepares them to actively contribute to society, in accordance with core Islamic values. The program also demonstrates the potential of a PAR-based approach to creating a sustainable and impactful model of religious education in schools.